Pengukuran Kinerja Puskesmas Dalam Rangka Peningkatan Layanan Kesehatan Masyarakat - Dhidik Apriyanto (Faculty of Social and Political Sciences, Universitas Diponegoro, 2016)
This reseach is an attempt to measure how the performance of health center services at Parit Haji Husein II Pontianak in order to improve public health services. The analysis tool used is a statistical method to determine the Cartesian diagram where the gap of each answer the questionnaire. While the variables used are five dimensions of service quality developed by Parasuraman et.al, with the acronym RATER namely Reliability, Assurance, Tangible, Empaty, and Responsiveness. The results of the analysis of Cartesian diagram of the five variables are: item questions coming in the position I was Diagnosis doctor precise and accurate, Caution patient satisfaction, skills of employees in the airport, Courtesy of services, Analysis Physicians who do not doubt, Analysis doctor is not at risk, doctors can be trusted Easy, consult a physician and employee, there is no obstacle in consultation with a doctor, Doctor with your info detail, doctor requested information to the patient about the complaint, Doctor responsive, Diagnosis physician accountable, Doctor listened well, doctor serving patients during hours work. While the services that go into quadrant II on the Compliance schedule open and close. And service entry in quadrant III is the speed of service, employee came right on time, good physical form health center, health center facilities complete, ready at the desk clerks, Means technology is already good, adequate waiting room chair. While the service entrance in quadrant IV is a doctor and staff give direction well and say hello to the visitor confused.